Nutrients, Fiber Fraction, and In Vitro Fiber Digestibility of Brown-Midrib Sorghum Mutant Lines Affected by The Maturity Stages - R. Sriagtula; P. D. M. H. Karti; L. Abdullah; Supriyanto; D. A. Astuti; Zurmiati (Faculty of Animal Science, Bogor Agricultural University, 2021)
The mutant line of Brown-midrib sorghum has lower lignin content than conventional sorghum. The objectives of this research were to investigate the effects of plant maturity stages at harvest times on nutrient, fiber fraction, tannin content, volatile fatty acids (VFA) production, and in vitro fiber digestibility of mutant lines of Brown Midrib (BMR) sorghum. This research was arranged into a complete block design with a factorial arrangement in three replications. The first factor was a line of BMR sorghum consisted of 3 levels, i.e., Patir 3.1 (non-BMR line/control), Patir 3.2 (BMR line), and Patir 3.7 (BMR line). The second factor was the generative stages of sorghum consisted of 3 levels, i.e., flowering stage, soft-dough stage, and hard-dough stage. The observed variables were nutrient, fiber fraction, tannin content, in vitro rumen fluid characteristics, VFA proportion, acetate: propionate (A:P) ratio, and in vitro fiber-fraction digestibility (IVFFD). Data were analyzed by Analysis of Variance (ANOVA) and Duncan’s Multiple Range Test (DMRT). No interaction between sorghum-mutant lines and harvest time on nutrient contents, except on total digestible nutrients (TDN), tannin, and VFA. The factor of sorghum-mutant line affected (p<0.01) crude protein (CP), crude fiber (CF), acid detergent fiber (ADF), lignin, neutral detergent fiber digestibility (NDFD), NH3, butyrate, isovalerate, and valerate. Maturity stages affected dry matter (DM), CF, ash, crude fat, fiber, and fraction, except hemicellulose, acid detergent fiber digestibility (ADFD), and NDFD, NH3, isovalerate, and valerate. Patir 3.7 at the hard-dough stage produced the highest TDN, but the highest VFA was produced by Patir 3.1 at flowering stages. BMR sorghum-mutant lines produced higher ADF digestibility than non-BMR sorghum-mutant lines. The increasing NDF digestibility was significantly influenced by both sorghum-mutant lines and maturity stages (p<0.01). It is concluded that BMR sorghum-mutant lines at the hard-dough stage produce better nutrient and in vitro digestibility, but the butyric acid is higher in non-BMR sorghum-mutant lines.